LAPAROSCOPIC LIVING DONOR NEPHRECTOMY IN INDONESIA - Mochtar, Chaidir Arif; Wahyudi, Irfan; Baskoro, Bagus (Indonesian Urological Association, 2014)
Objective: To evaluate and analyze variables related to the surgical and direct post-operative outcomes of our initial experience of laparoscopic living donor nephrectomies (LLDN). Material & methods: This retrospective analysis describes the first 10 laparoscopic nephrectomies in living donors performed in Cipto Mangunkusumo Hospital. All surgeries were performed by the same surgical team. Variables related to the surgical and post-operative outcome and complications in donors were evaluated and analyzed.Results: The average age of the donors was 31.8 years with male : female ratio of 7 : 3. Thirty percent of them were family related to the recipient. The left kidney was extracted from all patients and multiple renal vessels were found in one cases. The mean operation time was 321.9 ± 27 min, first warm ischemia time was 9.37 ± 3.34 min and estimated blood loss was 270 ± 182.87ml. The hospital stay was 4.1 ± 1.3 days, VAS in the first day post surgery was 3 ± 1 with epidural analgesia needed for 1.8 ± 0.6 days, and drain was kept in for 2.8 ± 1.2 days while urethral cathether for 2.4 ± 1.2. Time to return to work was 16 ± 8.4 days. Conclusion: LLDN results in acceptable blood loss,less post-operative pain, short hospital stay and short time to return to work for the donors, therefore promising to be the gold standard among living donor nephrectomy surgical options.Keywords: Laparoscopic living donor nephrectomy,renal transplantation, Indonesia.